Balance of Payments Imbalances, by Alan Greenspan. (International Monetary Fund, 2007)
This paper focuses on the developing countries, which accounted for nearly half the value of those surpluses, were apparently unable to find sufficiently profitable investments at home that overcame market and political risk. The United States a decade ago likely could not have run up today's near USD 800 billion annual deficit for the simple reason that we could not have attracted the foreign savings to finance it. In 1995, for example, total cross-border saving was less than USD 300 billion. The long-term updrift in this broader swath of unconsolidated deficits and mostly offsetting surpluses of economic entities has been persistent but gradual for decades, probably generations. However, the component of that broad set that captures only the net foreign financing of the imbalances of the individual US economic entities, our current account deficit, increased from negligible in the early 1990s to 6.2 percent of our GDP by 2006.